Prevalence of urban poor and its health related factors in the state of Selangor, Malaysia - Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal; Abdul Rahman, Hejar; Ahmad, Rozali; Abdullah, Mohd Yunus (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
The objectives of this study were to determine the prevalence of the urban poor and its health related factors in Selangor. This cross-sectional study was conducted in the community of Selangor. Data was collected from January 2006 to June 2006. Three out of nine districts were selected to be involved in the study, which were Klang, Kuala Langat and Petaling. A Multistage Stratified Proportionate Systematic Random Sampling was used for this study. The sampling was carried out by the Statistics Department of Malaysia. The survey frame was based on the information gathered from the Population and Housing Census in year 2000. The respondents were interviewed by trained research assistants using a structured pre-tested standardized questionnaire prepared in Malay and English languages. A monthly income of RM706 and less was used to define urban poor based on the guidelines given by the Economy Planning Unit of Malaysia (2004). SPSS 16.0 version was used to analyze the data. Out of 2535 respondents interviewed in this study, 2491 respondents answered the questionnaire completely (response rate 98.3%). Out of 2491 respondents, 202 (8.1%) had a monthly income of RM706 and less. Analysis of the urban poor respondents found that majority were aged between 18 to 40 years old (55.9%), and 29.7% had diagnosed medical illnesses, where hypertension, diabetes and asthma were the most common illnesses at 12.4%, 10.9% and 5.0% respectively. About 10% of the urban poor respondents had physical disabilities such as blurring of vision (7.9%), hearing problems (1.0%) and other disabilities (1.0%).